2014
DOI: 10.1353/jda.2014.0049
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Tendencies in an Emerging Capital Market: A Study of Individual Investors in India

Abstract: Recent findings in the finance and consumer behaviour literature have shown that investors' investment decisions are likely to be affected by their psychological tendencies. The focus of this paper is to understand how investors' psychological tendencies influence purchase postponement of shares. Furthermore, the moderating effects of product involvement on the relationship between psychological tendencies and also purchase postponement are examined. Using a survey research design, data was collected from Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…And these biases in turn may be a function of personal factors such as personality and attitude -especially attitude towards risk tolerance. Pandit and Yeoh (2014), in a study on Indian consumers, also found similar results and report that psychological factors such as risk propensity and consumer involvement have a significant effect on the purchasing decisions of individual investors in a developing capital market. The study concluded that, on one side, investment choices depend upon demographics like gender, age, income, education, occupation and, on the other side, it is also a function of risk tolerance of the investors.…”
Section: Predicting Investment Decisions: Role Of Demographic and Persupporting
confidence: 61%
See 2 more Smart Citations
“…And these biases in turn may be a function of personal factors such as personality and attitude -especially attitude towards risk tolerance. Pandit and Yeoh (2014), in a study on Indian consumers, also found similar results and report that psychological factors such as risk propensity and consumer involvement have a significant effect on the purchasing decisions of individual investors in a developing capital market. The study concluded that, on one side, investment choices depend upon demographics like gender, age, income, education, occupation and, on the other side, it is also a function of risk tolerance of the investors.…”
Section: Predicting Investment Decisions: Role Of Demographic and Persupporting
confidence: 61%
“…Numerous researches across the globe (Lewellen et al, 1977;Clark-Murphy and Soutar, 2005;Feng and Seasholes, 2008;Al-Ajmi, 2008;Kasilingam and Jayabal, 2010;Pandit and Yeoh, 2014) have conducted in-depth analysis by studying habits and practices of individual investors, their risk appetite and the decision-making process followed by them. On examining the available work done in the area one can cluster the papers on the basis of the research objectives as those that look at investment patterns and behaviours, while others that have attempted to understand the possible antecedents or factors that have a bearing on the direction of the decision taken.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…After the Establishment of SEBI Act (1992), which established SEBI as the regulator of Indian capital markets, the latter became more important. SEBI took many measures to attract investors to the market, including: reserving 35 per cent of share offerings for individual investors, 5 per cent discount on the share price and one lot to be worth between INR 10,000–15,000, up from INR 5,000–7,000 (Pandit and Yeoh, 2014; Mehta and Sondhi, 2016). In addition, SEBI has been conducting investor awareness programmes to encourage participation at an individual level (Business Standard, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…India is the number one populated country in the world, and investors' behavior is radically different from other countries (Pandit and Yeoh 2014). Indian investors tend to invest in their children's education, healthcare, and celebrations like marriage.…”
Section: The Study Context-indiamentioning
confidence: 99%